(3QSGdI aj JYQja GdYOO heGgjJgs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hHYO aEfc SCdJ Yf JYQja GdYOO hTQM eGgjJg aGYde HGQc Gddg ajce hdce(B_ (3Cf GdYOO eG GLJeY ef GdhMOGJ s
(3BNQgG (B:s
(3adPdc UM bhdfG jYfi RhL GdRhL hGdaQO GfJgi hcJH HChGMQ LeGOi GdKGfjI ef YGe (B1278 (3g` s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs